Flexible learning in a partnership context for beginning teachers - Brian M. Sova; Roger G. Hacker (Association for Learning Technology, 1998)
Universities have been slow to adapt to technological change. As the Teaching and Learning Committee of the University of Western Australia observe in Alternative Modes of Teaching and Learning (1996, 2): The new world that is emerging values flexibility over rigidity, and process over content. Yet with our complex system of faculties and departments, courses and units, curricula and assessment, we offer students little control over their own learning. Our current model is predominantly didactic rather than negotiated, and we prefer to control learning resources, rather than offer them. Our school system is already adapting, restructuring and adopting technology to make the curricula more relevant to individual learners' characteristics, to make learning more active, and to empower students to take responsibility for their own learning. Students will come to expect no less from their tertiary experiences.